2017
DOI: 10.1016/j.oraloncology.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Small cell carcinoma of the head and neck: An analysis of the National Cancer Database

Abstract: Purpose/Objective(s) To evaluate treatment trends and overall survival of patients with small cell carcinoma of the head and neck region. Materials/Methods Patients from 2004–2012 were identified from the National Cancer Database. Patient demographics and overall survival were analyzed. Multivariable analysis was used to identify predictors of survival. Results Among 347,252 head and neck patients a total of 1,042 (0.3%) patients with small cell carcinoma were identified. 17% of patients were diagnosed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
112
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(117 citation statements)
references
References 28 publications
(37 reference statements)
5
112
0
Order By: Relevance
“…SmCCHN occurs in nearly all structures of the head and neck and most frequently originates in the larynx . Accepted therapeutic modalities include surgical resection, radiation therapy, or chemotherapy, although a recent study showed that there is no therapeutic advantage to treating with surgery in addition to chemotherapy and radiation in locally advanced disease . The infrequent occurrence of this tumor in the head and neck makes it difficult for investigators to gain clinical experience treating these tumors or report more than limited personal experience or case studies.…”
Section: Introductionmentioning
confidence: 99%
“…SmCCHN occurs in nearly all structures of the head and neck and most frequently originates in the larynx . Accepted therapeutic modalities include surgical resection, radiation therapy, or chemotherapy, although a recent study showed that there is no therapeutic advantage to treating with surgery in addition to chemotherapy and radiation in locally advanced disease . The infrequent occurrence of this tumor in the head and neck makes it difficult for investigators to gain clinical experience treating these tumors or report more than limited personal experience or case studies.…”
Section: Introductionmentioning
confidence: 99%
“…According to epidemiological reports, SmCCs arise most frequently in the lung and extrapulmonary small cell carcinomas are rare, only accounting for 2-4% of all SmCCs. 1 SmCC of the salivary gland is an extremely rare and aggressive malignancy representing less than 1% of all salivary gland tumors. 2 SmCC of the salivary gland could occur in both the major and minor salivary glands, with most cases affecting the parotid glands.…”
Section: Introductionmentioning
confidence: 99%
“…SNEC accounts for only 11%–16% of all extrapulmonary small cell carcinomas, 2 and oropharyngeal tumors account for only 12.3% of all cancers in the head and neck. 6 SNEC often presents in older patients (age: 50–66 years) without sex bias; however, the majority of cases in the tonsil involve male patients, with a male to female ratio of 1.75:1. 10 Therefore, our current case is not consistent with the existing pattern.…”
Section: Discussionmentioning
confidence: 99%
“… 3 5 Many of the reported cases involved high-grade carcinomas, a highly invasive form of cancer with distant metastasis. 6 Some smaller series have reported that 14.5%–25% of patients present with distant metastatic disease. 7 , 8 Patients with a locally advanced stage and metastatic disease often have a low median survival rate, according to previous reports.…”
Section: Introductionmentioning
confidence: 99%